'Shine Bright Like a Diamond': music, performance and digitextuality in Céline Sciamma's Bande de filles (2014). Issue 4 (2nd October 2018) - McNeill, Isabelle
Abstract: This article examines the use of music in Céline Sciamma's Bande de filles ( Girlhood, 2014), a film depicting the experiences of a black girl and her friends growing up in the Parisian banlieue . In addition to music written for the soundtrack, the film features diegetic performances by its characters of globally popular songs, the dance routine Internet hit 'Wop' by J. Dash, and 'Diamonds' as performed by Rihanna. These performances not only occupy key narrative roles but also situate the film in relation to a widely familiar and/or accessible pop cultural landscape that encompasses an online visual imaginary or 'digitextuality' constructed through YouTube, Vevo and Vine videos circulating, sharing and responding to the songs and their video performances. This article examines the significance of weaving such sounds and images into the film's fictional world, aiming to understand the implications of this for questions of gender, sexuality and race raised by the film. Taken together with the film's wider aesthetic and musical choices, its digitextuality serves both to implicate the spectator and to frustrate a fixed view or reading of the characters. The result is a queer film that exposes the rigid lines of straight, white culture whilst also working to disorient them.